DIDACTIC SUPPORT FOR THE FORMATION OF SELF-CONTROL SKILLS IN FOREIGN TEXTBOOKS: ALTERNATIVE APPROACHES - D. Fedotova, Olga (Nuances: estudos sobre Educação, 2019)
The paper studies didactic approaches used to create self-test units in textbooks. The system of self-control skills formation is considered on the example of textbooks on reading. The authors define the approaches of textbooks published in Kyrgyzstan, Kazakhstan, Russia, the Netherlands, Germany, France and Greece in Cyrillic, Latin and Greek alphabets to the organization of self-control based on the content and structure. The didactic features of these publications are described from the viewpoint of realizing the possibility of self-test of the tasks and exercises. German and Greek textbooks with an original system of self-test in illustrative and textual form are singled out and analyzed in detail. The types of tasks for the thinking development in schoolchildren are distinguished with the use of cluster analysis. The content analysis helped the authors in identifying the five groups of multiple or single selection of objects and things tasks and exercises, reproduction of previously studied letters, sequencing, correlation, and design. The paper shows the similarities and differences in the implementation of self-control skills formation in various editions of textbooks. The separate unit of exercises for the development of fine motor skills are considered as a means of developing graphic accuracy and a prerequisite for the transition to the stage of logical thinking.